Reversible MR Findings in Marchiafava-Bignami Disease - Carmine Franco Muccio; Luca De Lipsis; Rossella Belmonte; Alfonso Cerase (Case Reports in Neurological Medicine)
Marchiafava-Bignami Disease (MBD) is a toxic demyelinating disease often diagnosed in chronic alcoholics. The disease process typically involves the corpus callosum and clinically presents with various manifestations resulting in MBD type A and type B on the basis of clinical condition, extent of callosal involvement and extracallosal involvement at brain magnetic resonance imaging (MRI), and prognosis. The death rate is high. We report a patient affected by MBD type B, who presented an isolated reversible splenial lesion at brain MRI and achieved a favorable recovery.